1993
DOI: 10.2527/1993.713663x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between porcine somatotropin and dietary lysine on growth performance and carcass characteristics of finishing swine2

Abstract: Seventy-two barrows (initial weight = 57.1 kg) were used to determine the interrelationship between porcine somatotropin (pST) and dietary lysine and their effects on growth performance and carcass characteristics. Pigs were injected daily in the extensor muscle of the neck with either 4 or 8 mg of pST and fed a pelleted corn-soybean meal-sesame meal diet (.8% lysine; 17.8% CP) or diets containing 1.0, 1.2, or 1.4% lysine provided by additions of L-lysine.HCl (2 x 4 factorial arrangement). Control pigs (placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 14 publications
2
9
1
Order By: Relevance
“…These changes are thought to be the consequences of increased muscle proteolysis. Liver (Goodband et al, 1993), which is in accordance with the positive correlation between obesity and BCAA concentration in plasma found in rodents and humans. p-ST treatment also decreased uremia and increased plasma glucose (Goodband et al, 1993) whatever the dietary lysine concentration, and the adipose tissue of p-ST-treated pigs became resistant to insulin.…”
Section: Rodent Models Of Obesitysupporting
confidence: 87%
“…These changes are thought to be the consequences of increased muscle proteolysis. Liver (Goodband et al, 1993), which is in accordance with the positive correlation between obesity and BCAA concentration in plasma found in rodents and humans. p-ST treatment also decreased uremia and increased plasma glucose (Goodband et al, 1993) whatever the dietary lysine concentration, and the adipose tissue of p-ST-treated pigs became resistant to insulin.…”
Section: Rodent Models Of Obesitysupporting
confidence: 87%
“…Several studies have reported lower carcass leanness and higher carcass fatness after a decrease in dietary protein supply (Karlsson et al, 1993;Essen-Gustavsson et al, 1994;Chiba et al, 2002) and/or lysine supply (Cromwell et al, 1993;Goodband et al, 1993;Castell et al, 1994;Kerr et al, 1995;Cisneros et al, 1996;Blanchard et al, 1999;Witte et al, 2000;Bidner et al, 2004). This was also evident in the present study.…”
Section: Growth Performance and Carcass Compositionsupporting
confidence: 84%
“…Feed intake, calculated cumulatively on a weekly basis, was not significantly influenced by pST or sex type in this study (Tables 2 and 3). This is in contrast with the findings of Goodband et al (1993) and Klindt et al (1995) who found a decrease in feed intake for animals treated with pST and fed diets with increased levels of lysine. Klindt et al (1995) also found a dose-dependent decrease in feed intake of boars and gilts slaughtered between 81.1 and 94.4 kg.…”
Section: Resultscontrasting
confidence: 99%